Merancang Sistem Penarik pada Mesin Pemarut Singkong Menggunakan VDI 2221 - Nanda Pranandita; Muhammad Yunus (Manutech : Jurnal Teknologi Manufaktur, 2021)
Cassava is a multipurpose plant. Apart from being used as a daily snack, cassava is also used as raw material for various industries. Currently, cassava processing technology has varied. One of them is a grating machine. The grating machine is used in order to make cassava into cassava pulp. In this research, the design of a cassava grater machine will be carried out. The design that is carried out focuses on the pulling system in the grated process. The design method used is VDI 2221. The stages in VDI 2221 are clarification of the task, conceptual design, embodiment concept, detailed design. Based on the results of the design carried out, several conclusions can be drawn, namely the chosen concept uses three towing rollers, a gear and a sprocket as a transmission roller pulling motion, while the gap control system uses bolts as the regulator. In addition, after carrying out the loading analysis on the shaft to be used as a towing roll, a roller with a size of Ø20mm can be used because the loading simulation results show that the maximum torsional stress value that occurs is 4.601 N / mm2 which is still much smaller than the value of the permitted torsional stress.